Behavior of High-plasticity Clay Stabilized with Lime and Rice Husk Ash - Fatnanta, Ferry; Nugroho, Soewignjo Agus; Ongko, Andarsin; Ihsan, Adnan Ruziq (Makara Journal of Technology, 2021)
Soil is an important and fundamental element for building and road construction. However, poor properties of soil can affect the entire construction since the soil will resist the loads transferred from the upper structures. Additives such as cement, lime, and rice husk ash (RHA) can be used as stabilization materials to increase soil strength. This study examined the behavior of stabilized plastic clay mixed with cement, lime, and RHA. The clay stabilization success rate can be measured by the California Bearing Ratio (CBR), unconfined compression strength, and swelling potential. In this study, different mixtures were prepared as samples and tested under various loads: 1, 2, 3, 4, and 5 kPa. The results indicated that the addition of cement, lime, and RHA could effectively reduce the swelling potential of clay. The mixture variations of soil–cement composite 90% + RHA 10% and soil–cement composite 90% + lime 4% + RHA 6% showed the lowest swelling rate.